Productivity, water and nitrogen utilization of intensified dryland farming with annual forages on the Chinese Loess plateau - Deng, Jianqiang; Zhang, Zhixin; Usman, Samaila; Yang, Xianlong; An, Dong; Shen, Yuying (Frontiers in Sustainable Food Systems, 2023)
Understanding the relationships of productivity performance and water utilization and soil nitrogen dynamics after annual forage planting during the fallow period (F) in winter wheat (Triticum aestivum L.; W) mono-cropping is critically important for maintaining sustainable livestock and grain production in semiarid regions. We used 2 years (2017–2019) of data to investigate soil nitrogen dynamics, production, water utilization, and fallow efficiency when forage rape (Brassica campestris L.; R) and common vetch (Vicia sativa L.; V) were planted in a 3-month summer fallow of the W-F-W-F cropping system. Three cropping systems were comprised of winter wheat-summer fallow-winter wheat-summer fallow (W-F-W-F), winter wheat-forage rape-winter wheat-forage rape (W-R-W-R), and winter wheat-forage rape-winter wheat-common vetch (W-R-W-V). The results showed that the annual forage planting decreased the average NO3−-N content by 54.8% compared with the W-F-W-F cropping system. Compared with the W-F-W-F cropping system, planting annual forage in summer fallow increased the average system forage production by 4.93 t ha−1. Local total annual precipitation can meet crop-water requirements, and the limiting factor for agricultural production was the drought due to the uneven seasonal distribution of precipitation. In comparison to the W-F-W-F cropping system, annual forage planting decreased the average available soil moisture storage by 50.3 mm above the 80 cm soil layer. Compared with that in the W-R-W-R (23.21 t ha−1) and W-F-W-F (30.25 t ha−1) cropping systems, the crop productivity in the W-R-W-V cropping system (33.23 t ha−1) was relatively stable and high because the reduction in subsequent winter wheat yield (2.96 t ha−1) was adequately offset by the forage yield (5.15 t ha−1). Adding forage rape to the W-F-W-F cropping system decreased system crop-water productivity (CWP) by 40.9%. However, the CWP, precipitation use efficiency (PUE), and soil nitrate in the W-R-W-V cropping system increased by 30.4, 30.1, 110.9, and 82.0%, respectively, compared with those in the W-R-W-R cropping system. Therefore, the W-R-W-V cropping system is recommended for better water and fertility management as well as grain and forage production in semiarid regions. However, further study is required to involve drought years for better evaluation of the effect of long-term precipitation variability on the crop productivity.